2010
DOI: 10.1002/cphc.200900817
|View full text |Cite
|
Sign up to set email alerts
|

Platinum and Non‐Platinum Nanomaterials for the Molecular Oxygen Reduction Reaction

Abstract: Herein, some chemical approaches to the tailoring of nanodivided materials are highlighted. Transition-metal materials in nanodivided form are essentially devoted to study the electrocatalytic reduction of molecular oxygen (ORR) in acid medium. This Minireview focuses on the physical and chemical structures of platinum-based and non-platinum-based materials. Due to the research dynamism in this field, the discussion is limited to a comprehensive review of ORR cathode materials investigated in the author's labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 136 publications
5
54
0
Order By: Relevance
“…At low potentials, the surface is covered with O 2 H radicals, eventually fully. This accumulation may be followed by the formation of hydrogen peroxide, which was observed by many authors [25,26], even if it is energetically unfavorable, in accordance with the DFT calculations. If the zero coverage region is too wide, i.e., the formation of O 2 H radicals would overlap with the hydrogen underpotential deposition region, the coverage with respect to O 2 H species might be much lower or nonexistent due to the following reaction:…”
Section: Resultssupporting
confidence: 82%
“…At low potentials, the surface is covered with O 2 H radicals, eventually fully. This accumulation may be followed by the formation of hydrogen peroxide, which was observed by many authors [25,26], even if it is energetically unfavorable, in accordance with the DFT calculations. If the zero coverage region is too wide, i.e., the formation of O 2 H radicals would overlap with the hydrogen underpotential deposition region, the coverage with respect to O 2 H species might be much lower or nonexistent due to the following reaction:…”
Section: Resultssupporting
confidence: 82%
“…Since the hydrogen peroxide generated on the surface of the ring electrode decreases from 30% to 15% when the loading rate is changed from 20 wt % to 50 wt %, there must exist a limiting catalytic site density. A similar trend was observed in other systems, e.g., 20 wt % Ru x Se y /C, which overpasses the current density of 70 wt % Ru x Se y /C [100], including Pt/C [101].…”
Section: Non-precious Catalystssupporting
confidence: 86%
“…A similar trend was observed in other systems, e.g., 20 wt % RuxSey/C, which overpasses the current density of 70 wt % RuxSey/C [100], including Pt/C [101]. Besides the ORR activity on the Co-Se system, the methanol tolerance was further investigated in alkaline medium [102].…”
Section: Non-precious Catalystssupporting
confidence: 78%
“…Previous works demonstrated that this method is powerful to control the size (ca. 2-5 nm) and morphology of Pt-based NPs without surface faceting (spherical NPs) [15,16]. The particle size and morphology are controlled via the formation of clusters di-anions [Pt 3 (CO) 6 ] n 2À under CO atmosphere, which then decompose and release Pt NPs [15,16].…”
Section: Introductionmentioning
confidence: 99%